Stevioside Prevents Wear Particle-Induced Osteolysis by Inhibiting Osteoclastogenesis and Inflammatory Response via the Suppression of TAK1 Activation - Meng, Jiahong; Zhou, Chenhe; Hu, Bin; Luo, Mengmeng; Yang, Yute; Wang, Yangxin; Wang, Wei; Jiang, Guangyao; Hong, Jianqiao; Li, Sihao; Wu, Haobo; Yan, Shigui; et al. (Frontiers in Pharmacology, 2018)
Aseptic loosening and periprosthetic osteolysis are the leading causes of total joint arthroplasty failure, which occurs as a result of chronic inflammatory response and enhanced osteoclast activity. Here we showed that stevioside, a natural compound isolated from Stevia rebaudiana, exhibited preventative effects on titanium particle-induced osteolysis in a mouse calvarial model. Further histological assessment and real-time PCR analysis indicated that stevioside prevented titanium particle-induced osteolysis by inhibiting osteoclast formation and inflammatory cytokine expression in vivo. In vitro, we found that stevioside could suppress RANKL-induced osteoclastogenesis and titanium particle-induced inflammatory response in a dose-dependent manner. Mechanistically, stevioside achieved these effects by disrupting the phosphorylation of TAK1 and subsequent activation of NF-κB/MAPKs signaling pathways. Collectively, our data suggest that stevioside effectively suppresses osteoclastogenesis and inflammatory response both in vitro and in vivo, and it might be a potential therapy for particle-induced osteolysis and other osteolytic diseases.